Impact of the COVID-19 pandemic on cardiology services at a tertiary cardiac centre in a low- and middle-income country in Asia. (14th October 2021) - Cader, F A; Chowdhury, I Z; Haq, M M; Chowdhury, M Z; Khan, S R
Abstract: Background: The COVID-19 pandemic resulted in reduced numbers of patients presenting with and undergoing procedures for cardiac conditions worldwide. This impact, specifically looking at the changes in patient visits, admissions and procedure volumes, has not been recorded thus far, in terms of a South Asian LMIC setting. Purpose: We aimed to assess the impact of the pandemic on emergency room (ER) visits, cardiology admissions, out-patient and in-patient procedures at a LMIC tertiary cardiac centre. Methods: Data on ER visits, specific in-patient and out-patient procedures (echocardiography, exercise stress tests, electrocardiography [ECG]) were collected via hospital electronic records from January to December 2020, and compared with corresponding data for the same months in 2019. The difference or deficits were expressed as a percentage (%Δ). Data for each quarter were compared using paired t-test. A p value <0.05 was considered significant. Results: There were significantly reduced numbers of out-patient visits (Δ −31.2%; p=0.007), ER visits (%Δ −59.5%; p=0.0), in-patient admissions (Δ −33.1%; p=0.005), total out-patient procedures (%Δ −31.9%; p=0.008) and catheterization volumes (%Δ-29.7%; p=0.001) in 2020, as compared with 2019 (Table 1 & Figure 1). Among out-patient procedures, adult trans-thoracic echo, ECG and stress tests showed greatest deficits in April 2020. No trans-oesophageal echocardiograms were performed in April to July 2020. The greatest deficits were observed in April 2020, as compared with 2019 (out-patient visits: Δ-92.7%; out-patient procedures: %Δ-94.5%; in-patient admissions: %Δ-85.9%; catheterization procedures: %Δ-85.2%), except for ER visits, where the greatest deficit was seen in June 2020: %Δ-90.7%). Numbers continued to remain extremely low in May 2020, coinciding with the nation-wide lockdown measures. Out-patient visits, procedures and in-patient admissions have gradually increased since July 2020. However, the greatest impact seems to have been on ER visits, continued to remain low, with significantly reduced volumes in both 2nd and 3rd quarters of 2020. The lowest deficits in outpatient visits (Δ-4.9%), ER visits (Δ-31.9%) and out-patient procedures (Δ-0.9%) were seen in December 2020, while for in-patient admissions (Δ-7.9%) and catheterization procedures (Δ-6.5%) this was in October 2020. Conclusion: There was a significant reduction of out-patient and in-patient cardiology services volumes in 2020, with the greatest reduction in April and May, coinciding with a general "lockdown". ER visits were the most greatly affected. Trends show a steady increase in out-patient and catheterization procedures, beginning from July, but have not yet reached pre-COVID volumes, even by the end of 2020. These findings indicate that, the pandemic has resulted in significantly fewer ER visits; however, patients still present as outpatients, both for procedures and catheterization. FUNDunding Acknowledgement: Type of funding sources: None.